2011
DOI: 10.3390/s110908550
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Long-Period Fiber Grating Sensor Platform for Chloride Ion Concentration Measurement

Abstract: Optical fiber sensors based on waveguide technology are promising and attractive in chemical, biotechnological, agronomy, and civil engineering applications. A microfluidic system equipped with a long-period fiber grating (LPFG) capable of measuring chloride ion concentrations of several sample materials is presented. The LPFG-based microfluidic platform was shown to be effective in sensing very small quantities of samples and its transmitted light signal could easily be used as a measurand. The investigated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 52 publications
(67 reference statements)
0
19
0
Order By: Relevance
“…At present, as an RI sensor, the LPFG has been used to monitor ethylene glycol concentration [3], dimethylsulfoxide [4], olive oil [5], chloride ion concentration [6], Escherichia coli bacteria [7], organic aromatic compounds [8], hydrocarbons [9], etc. However, in order to exploit and extend the application in the biological and chemical molecular detection, the sensitivity of LPFGs still needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…At present, as an RI sensor, the LPFG has been used to monitor ethylene glycol concentration [3], dimethylsulfoxide [4], olive oil [5], chloride ion concentration [6], Escherichia coli bacteria [7], organic aromatic compounds [8], hydrocarbons [9], etc. However, in order to exploit and extend the application in the biological and chemical molecular detection, the sensitivity of LPFGs still needs to be further improved.…”
Section: Introductionmentioning
confidence: 99%
“…With their enhanced RI sensitivity, LPFG-based devices for chemical concentration measurements were developed [15,16]. The previous research studies demonstrated that LPFG sensors possess high sensitivity and accuracy for environmental RI detection.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the optical signal was further directed through the optical fiber to the back-end signal capture device for photoelectric signal conversion and processing. The microfluidic chip was made of poly(methyl methacrylate): PMMA (chip size: 50 × 20 × 8 mm; micro-channel size: 50 × 1 × 0.9 mm) and fabricated using a computer numerical control engraving machine by our group [21]. The sensing fiber was packaged inside the microfluidic chip.…”
Section: Methodsmentioning
confidence: 99%